2023
DOI: 10.1002/hbm.26258
|View full text |Cite
|
Sign up to set email alerts
|

Using graph theory as a common language to combine neural structure and function in models of healthy cognitive performance

Abstract: Graph theory has been used in cognitive neuroscience to understand how organisational properties of structural and functional brain networks relate to cognitive function. Graph theory may bridge the gap in integration of structural and functional connectivity by introducing common measures of network characteristics. However, the explanatory and predictive value of combined structural and functional graph theory have not been investigated in modelling of cognitive performance of healthy adults. In this work, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Garai et al highlighted that network patterns or topological features in structural connectivity possess predictive power for human cognitive traits [36]. While Litwińczuk observed no consistent advantage in utilizing graph theory measures over connectivity values for explaining and predicting cognitive functions in healthy and typical domains, they noted instances where nodal graph theory metrics of the structural network outperformed raw connectivity models in predictive ability [37]. These prior studies support that the enhanced prediction accuracy observed with matrices synthesized by TG GAN II can be attributed to their graph theoretical features, which are more akin to those of the acquired matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Garai et al highlighted that network patterns or topological features in structural connectivity possess predictive power for human cognitive traits [36]. While Litwińczuk observed no consistent advantage in utilizing graph theory measures over connectivity values for explaining and predicting cognitive functions in healthy and typical domains, they noted instances where nodal graph theory metrics of the structural network outperformed raw connectivity models in predictive ability [37]. These prior studies support that the enhanced prediction accuracy observed with matrices synthesized by TG GAN II can be attributed to their graph theoretical features, which are more akin to those of the acquired matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies included in the current review, LOOCV was the most widely adopted (21 studies), while most other studies used 10-fold CV (10 studies). Although a recent study suggested that repetitive cross-validation is more reliable than the leave-one-out method (Valente et al, 2021), this technique was only adopted in three studies (Litwińczuk et al, 2023;Nemmi et al, 2023;Torres-Ramos et al, 2020). Overall, there is wide variability in the machine-learning techniques used in neuroimaging studies, both in terms of algorithm selection and CV method.…”
Section: Studies Use a Range Of Machine Learning Methodsmentioning
confidence: 99%
“…Graph theory, utilizing fMRI, quantifies brain connectivity, identifying regions contributing to cognitive functions like language processing with potential applications in neurological treatments, including aphasia [20]. Graph theory integrates neural structure and function for precise cognitive models, validated using fMRI in language tasks, predicting individual differences and identifying crucial brain regions for cognitive performance [21]. The study emphasizes vital QC procedures using the CONN toolbox for accurate fcMRI results, demonstrating effectiveness in artifact removal and improving connectivity accuracy in healthy participants.…”
Section: Prior Research Workmentioning
confidence: 99%